Method for regulating and controlling ECC volume stability by adopting CFB ash

By using CFB ash slag in ECC materials to regulate volume stability, and using its high sulfur content and porous structure to combine with cement and fiber, the problems of shrinkage and microcracking of ECC materials during long-term use are solved, significantly improving the durability of the material and stability, and provide a way to recycling CFB ash slag.

CN119390409AActive Publication Date: 2025-02-07WUHAN UNIV OF TECH

Patent Information

Application Number
CN202411467012.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-02-07
Estimated Expiration
2044-10-21

AI Technical Summary

Technical Problem

Existing ECC materials may experience shrinkage and microcracks during long-term use, affecting their structural integrity and durability, and the physical and chemical properties of traditional gelling materials limit the volume stability of ECC.

Method used

CFB ash slag is used to regulate the ECC volume stability. By mixing cement, CFB ash slag, fly ash with fine aggregate, adding water, water reducer and polymer emulsion, stirring evenly, fibers are added to form a modified ECC material. The high sulfur content and porous structure of CFB ash slag combine with cement and fiber to improve through chemical reactions and physical structures, reducing shrinkage and enhancing toughness.

Benefits of technology

It significantly improves the volume stability and shrinkage resistance of ECC, reduces the formation of shrinkage cracks, improves the durability and stability of the material, and provides a new way for the recycling and utilization of CFB ash slag, which is environmentally friendly and resource reuse. Advantages.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a method for regulating and controlling the volume stability of ECC by adopting CFB ash, which comprises the following steps: (1) mixing cement, CFB ash, fly ash and fine aggregate, and uniformly stirring to obtain a dry material; (2) mixing water, a water reducing agent and a polymer emulsion, adding the mixture into the dry material, and uniformly stirring to obtain slurry; and adding fibers into the slurry, and stirring until the fibers are completely dispersed to obtain the modified ECC material. The invention provides a method for regulating and controlling the volume stability of ECC by adopting CFB ash. The method can improve the volume stability of ECC.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of engineering cement composite materials, and in particular relates to a method for regulating the volume stability of ECC by using CFB ash. Background Art

[0002] As an advanced combustion technology, circulating fluidized bed (CFB) technology has been widely used in the fields of energy and environment. The byproducts of the CFB process - CFB ash (including fly ash and slag) may contain heavy metals and other toxic chemicals. If these substances seep into the soil or water, they may cause water and soil pollution. In addition, if the fine particulate matter in the ash is directly discharged into the air, it will increase air pollution. The annual emission of circulating fluidized bed fly ash and slag in my country is about 80 million tons. How to recycle CFB ash has become an ecological problem that needs to be solved urgently.

[0003] Engineered cementitious composites (ECC) are widely used in the fields of construction and civil engineering due to their excellent mechanical properties and durability. However, ECC materials may shrink and develop microcracks during long-term use, which will affect their structural integrity and durability. Therefore, improving the volume stability of ECC is the key to improving its application performance.

[0004] Conventional ECC usually uses fly ash as a cementitious material and ordinary fine aggregate. Although fly ash increases the workability and certain performance aspects of ECC, some of its own physical and chemical properties limit the performance of ECC in terms of volume stability.

[0005] CFB ash has high sulfur content and good water storage capacity, which makes it a potential material for improving the shrinkage properties of ECC. These unique properties of CFB ash provide new possibilities for the improvement of ECC, especially in improving the volume stability and anti-shrinkage properties of ECC. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a method for regulating the volume stability of ECC by using CFB ash in view of the deficiencies of the prior art, and the method can improve the volume stability of ECC.

[0007] The technical solution adopted by the present invention to solve the above-mentioned problems is:

[0008] A method for regulating the volume stability of ECC using CFB ash, characterized by comprising the following steps:

[0009] (1) Mix cement, CFB ash, fly ash and fine aggregate, and stir evenly to obtain dry material;

[0010] (2) mixing water, a water reducing agent and a polymer emulsion, adding the mixture to the dry material, and stirring the mixture to obtain a slurry; adding fibers to the slurry, and stirring the mixture until the fibers are completely dispersed to obtain a modified ECC material;

[0011] The CFB ash is one of CFB fly ash and CFB slag or a mixture thereof; the SO3 content in the CFB fly ash is 3-10wt%, and the SO3 content in the CFB slag is 2-18wt%; and the polymer emulsion is polyethylene-vinyl acetate emulsion.

[0012] In the above scheme, the raw materials are calculated by weight and include: 20-40 parts of cement, 10-40 parts of CFB ash, 10-50 parts of fly ash, 15-40 parts of fine aggregate, 20-30 parts of water, 0.1-1 parts of water reducer, 1-2 parts of fiber, and 3-10 parts of polymer emulsion.

[0013] In the above scheme, the CFB ash is a mixture of CFB fly ash and CFB slag, and the mass ratio of the CFB fly ash to the CFB slag is (2-3):1.

[0014] In the above scheme, the specific surface area of ​​the CFB fly ash is 300-700m 2 / kg.

[0015] In the above scheme, the particle size of the CFB fly ash is less than 0.1 mm; the particle size of the CFB slag is less than 4.75 mm. Compared with other cementitious materials, CFB fly ash has a stronger water storage capacity; CFB slag has a high calcium and sulfur content and is used to replace fine aggregate to improve the volume stability of ECC.

[0016] In the above scheme, the cement is any one of Portland cement and ordinary Portland cement.

[0017] In the above solution, the fine aggregate includes any one of quartz sand, natural sand and artificial sand.

[0018] In the above scheme, the water reducer is a polycarboxylic acid-based water reducer.

[0019] In the above scheme, the fiber is a PVA fiber with a diameter of 39 microns and a length of 10-15 mm.

[0020] In the above scheme, the fly ash is Class I fly ash.

[0021] The present invention also claims to protect the modified ECC material obtained by the method of regulating the volume stability of ECC using CFB ash.

[0022] In the present invention, in view of the common shrinkage problem of ECC, the method provided by the present invention utilizes the high sulfur content and the unique porous structure of CFB ash to optimize the performance of ECC, wherein the CFB ash includes CFB fly ash and CFB slag. The sulfur trioxide (SO3) component in the CFB ash can react with the calcium hydroxide produced during the cement hydration process to form ettringite. This reaction not only consumes free water and slows down the evaporation rate of water, but also forms a more stable structure by increasing the volume of the hydration product, thereby effectively reducing shrinkage. In addition, the formation of ettringite enhances the toughness of ECC, enables the material to better absorb and disperse external loads under stress, reduces stress concentration caused by drying and temperature changes, and reduces the formation of shrinkage cracks. The porous characteristics of CFB ash enable fibers and polymer emulsions to penetrate deeper into the microscopic pores of the material, improving the bonding between the cement matrix and the reinforcing material. The polymer emulsion (polyethylene-vinyl acetate emulsion) forms a mesh structure in ECC, which enhances the bonding between the cement matrix and the fiber, helping to improve the toughness of the concrete. When combined with the porous structure of CFB ash, the polymer emulsion can better penetrate and fill the pores. This improved bonding performance helps to retain internal moisture, thereby further reducing shrinkage. Therefore, the use of CFB ash in ECC not only optimizes the microstructure of the material, but also significantly improves its durability and stability.

[0023] In the present invention, CFB fly ash replaces cementitious materials at a replacement ratio of 0-50%, wherein the cementitious materials include cement and fly ash, so as to improve the shrinkage resistance of ECC; CFB slag is used as fine aggregate of ECC to reduce the volume change of ECC by utilizing its porosity; the volume stability of ECC is optimized by adjusting the ratio of CFB fly ash and CFB slag in CFB slag; the sulfur content in CFB slag is utilized to improve the early strength and durability of ECC through chemical reaction; and the ratio of cement to CFB slag is optimized to improve the overall performance of ECC.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] (1) The present invention provides a method for regulating the volume stability of ECC by using CFB ash, wherein the volume stability of ECC is regulated by adding CFB ash, wherein the CFB ash is divided into CFB fly ash and CFB slag, the CFB fly ash replaces cement and fly ash as a cementitious material, and the CFB slag replaces quartz sand as a fine aggregate; the method mainly utilizes the characteristics of CFB ash being porous and having a high sulfur content to achieve the effect of regulating the volume stability of ECC; and the obtained modified ECC material is suitable for various buildings and engineering structures requiring high volume stability.

[0026] (2) The method of using CFB ash to regulate the volume stability of ECC provided by the present invention provides a new way to recycle CFB ash, which is conducive to environmental protection and resource recycling; and the raw material source is wide, the cost is low, and the process is simple. DETAILED DESCRIPTION

[0027] The technical solution of the present invention will be fully and clearly described below in conjunction with specific embodiments, but the described embodiments are only some embodiments of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.

[0028] In a specific embodiment, the cement used is 42.5 grade ordinary Portland cement; the fine aggregate is quartz sand; the fiber is PVA fiber with a diameter of 39 microns and a length of 12 mm; the fly ash is Class I fly ash; the CFB fly ash and CFB slag are both taken from a thermal power plant in Shanxi Province, the particle size of the CFB fly ash is less than 0.1 mm, the particle size of the CFB slag is less than 4.75 mm, the SO3 content in the CFB fly ash is 7.66wt%, and the specific surface area is 300-700m 2 / kg; the SO3 content in the CFB slag is 2-13.86wt%.; the water reducer is HPWR-AUHPC60-1 type water reducer, which is a high-efficiency polycarboxylic acid water reducer; and the polymer emulsion is polyethylene-vinyl acetate emulsion.

[0029] Example 1

[0030] This embodiment provides a method for regulating the volume stability of ECC using CFB ash, comprising the following steps:

[0031] Accurately weigh 2.24kg of cement, 1.096kg of fly ash, 1.644kg of CFB fly ash, 1.79kg of quartz sand, 0.104kg of fiber, 1.30kg of water, 0.060kg of water reducer, and 0.498kg of polymer emulsion. First, mix the cement, fly ash, and CFB fly ash evenly, then gradually add the quartz sand and continue mixing until the dry materials are mixed evenly. Premix the water and water reducer, and slowly add the water, water reducer, and polymer emulsion to the dry materials during the mixing process. Continue stirring to ensure that the cement, fly ash, CFB fly ash, quartz sand, water, water reducer, and polymer emulsion are fully mixed to form a uniform slurry. Finally, add the fiber and continue stirring until the fiber is fully dispersed, ensuring that the fiber is evenly distributed in the mixture to avoid agglomeration.

[0032] The modified ECC samples were prepared according to the above production process, cast in 100mm×100mm×400mm, 150mm×150mm×150mm and 100mm×100mm×320mm molds, and cured for 24h under standard conditions. The shrinkage performance, compression performance and flexural performance of the samples were tested respectively. The shrinkage performance was measured by marking reference points at both ends or sides of the specimens. These reference points will be used for subsequent length measurements. The specimens were placed in an environment with a relative humidity of 50% for further curing, and the shrinkage performance was measured for 28 days.

[0033] Example 2

[0034] This embodiment provides a method for regulating the volume stability of ECC using CFB ash, comprising the following steps:

[0035] Accurately weigh 2.24kg of cement, 2.74kg of fly ash, 1.074kg of quartz sand, 0.716kg of CFB slag, 0.104kg of fiber, 1.30kg of water, 0.060kg of water reducer, and 0.498kg of polymer emulsion. First, mix the cement, fly ash, and CFB fly ash evenly, then gradually add the quartz sand and continue mixing until the dry materials are mixed evenly. Premix the water and water reducer, and slowly add the water, water reducer, and polymer emulsion to the dry materials during the mixing process. Continue stirring to ensure that the cement, fly ash, quartz sand, CFB slag, water, water reducer, and polymer emulsion are fully mixed to form a uniform slurry. Finally, add the fiber and continue stirring until the fiber is fully dispersed, ensuring that the fiber is evenly distributed in the mixture to avoid agglomeration. The modified ECC samples were prepared according to the above production process, cast in 100mm×100mm×400mm, 150mm×150mm×150mm and 100mm×100mm×320mm molds, and cured for 24h under standard conditions. The shrinkage performance, compression performance and flexural performance of the samples were tested respectively. The shrinkage performance was measured by marking reference points at both ends or sides of the specimens. These reference points will be used for subsequent length measurements. The specimens were placed in an environment with a relative humidity of 50% for further curing, and the shrinkage performance was measured for 28 days.

[0036] Example 3

[0037] This embodiment provides a method for regulating the volume stability of ECC using CFB ash, comprising the following steps:

[0038] Accurately weigh 2.24kg of cement, 1.918kg of fly ash, 2.062kg of quartz sand, 0.822kg of CFB fly ash, 0.358kg of CFB slag, 0.104kg of fiber, 1.30kg of water, 0.060kg of water reducer, and 0.498kg of polymer emulsion. First, mix the cement, fly ash, and CFB fly ash evenly, then gradually add the quartz sand and continue mixing until the dry materials are mixed evenly. Premix the water and water reducer, and slowly add the water, water reducer, and polymer emulsion to the dry materials during the mixing process. Continue stirring to ensure that the cement, fly ash, CFB fly ash, quartz sand, CFB slag, water, water reducer, and polymer emulsion are fully mixed to form a uniform slurry. Finally, add the fiber and continue stirring until the fiber is fully dispersed, ensuring that the fiber is evenly distributed in the mixture to avoid agglomeration.

[0039] The modified ECC samples were prepared according to the above production process, cast in 100mm×100mm×400mm, 150mm×150mm×150mm and 100mm×100mm×320mm molds, and cured for 24h under standard conditions. The shrinkage performance, compression performance and flexural performance of the samples were tested respectively. The shrinkage performance was measured by marking reference points at both ends or sides of the specimens. These reference points will be used for subsequent length measurements. The specimens were placed in an environment with a relative humidity of 50% for further curing, and the shrinkage performance was measured for 28 days.

[0040] Comparative Example 1

[0041] The preparation method of this comparative example is basically the same as that of Example 1, except that: CFB fly ash is not added, and the amount of each raw material used is: 2.24 kg of cement, 2.74 kg of fly ash, 1.79 kg of quartz sand, 0.104 kg of fiber, 1.30 kg of water, 0.060 kg of water reducer, and 0.498 kg of polymer emulsion.

[0042] Comparative Example 2

[0043] The preparation method of this comparative example is basically the same as that of comparative example 1, except that zeolite is used to replace the same amount of quartz sand, and the amount of each raw material used is: 2.24 kg of cement, 2.74 kg of fly ash, 1.79 kg of zeolite, 0.104 kg of fiber, 1.30 kg of water, 0.060 kg of water reducer, and 0.498 kg of polymer emulsion.

[0044] The data of the shrinkage performance, compression performance and flexural performance of the samples prepared in Examples 1-3, Comparative Example 1 and Comparative Example 2 are shown in Table 1.

[0045] Table 1

[0046] Test items Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 <![CDATA[Drying shrinkage × 10 -6 (με)]]> 319 216 157 1262 713 Compressive strength(MPa) 69 62 56 41 52 Flexural strength(MPa) 23 24 27 17 14

[0047] It can be seen from the test results in Table 1 that the modified ECC material prepared by the technical solution of the present invention can significantly reduce the shrinkage performance, while increasing the compressive strength and flexural strength. Compared with the traditional ECC material, the drying shrinkage of the ECC mixed with CFB ash is significantly reduced, and it has broad application prospects in the field of building materials.

[0048] In summary, the method for regulating the volume stability of ECC using CFB ash provided by the present invention can improve the volume stability of ECC.

[0049] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solution and its improved conception within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for regulating the volume stability of ECC using CFB ash, characterized in that: The following steps are involved: (1) Mix cement, CFB ash, fly ash and fine aggregate, and stir evenly to obtain dry material; (2) mixing water, a water reducing agent and a polymer emulsion, adding the mixture to the dry material, and stirring the mixture to obtain a slurry; adding fibers to the slurry, and stirring the mixture until the fibers are completely dispersed to obtain a modified ECC material; The CFB ash is one of CFB fly ash and CFB slag or a mixture thereof; the SO3 content in the CFB fly ash is 3-10wt%, and the SO3 content in the CFB slag is 2-18wt%; and the polymer emulsion is polyethylene-vinyl acetate emulsion.

2. A method for regulating ECC volume stability using CFB ash according to claim 1, characterized in that: The raw materials are calculated by weight and include: 20-40 parts of cement, 10-40 parts of CFB ash, 10-50 parts of fly ash, 15-40 parts of fine aggregate, 20-30 parts of water, 0.1-1 parts of water reducing agent, 1-2 parts of fiber, and 3-10 parts of polymer emulsion.

3. The method for controlling the volume stability of ECC using CFB ash according to claim 1, characterized in that: The CFB ash is a mixture of CFB fly ash and CFB slag, and the mass ratio of the CFB fly ash to the CFB slag is (2-3):

1.

4. The method for controlling the volume stability of ECC using CFB ash according to claim 1, characterized in that: The specific surface area of ​​the CFB fly ash is 300-700m 2 / kg.

5. The method for controlling the volume stability of ECC using CFB ash according to claim 1, characterized in that: The particle size of the CFB fly ash is less than 0.1 mm; the particle size of the CFB slag is less than 4.75 mm.

6. The method for controlling the volume stability of ECC using CFB ash according to claim 1, characterized in that: The cement is any one of silicate cement and ordinary silicate cement; the fine aggregate includes any one of quartz sand, natural sand and artificial sand.

7. The method for controlling the volume stability of ECC using CFB ash according to claim 1, characterized in that: The water reducing agent is a polycarboxylic acid water reducing agent.

8. The method for controlling the volume stability of ECC using CFB ash according to claim 1, characterized in that: The fly ash is Class I fly ash.

9. The method for controlling the volume stability of ECC using CFB ash according to claim 1, characterized in that: The fibers are PVA fibers, with a diameter of 39 microns and a length of 10-15 mm.

10. A modified ECC material obtained by the method of regulating the volume stability of ECC using CFB ash according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Anti-crack mortar containing sulfur fixation ash, and preparation and use methods thereof

    CN109020396A

  • Interface mortar with sulfur fixation ash and preparation and application methods thereof

    CN109694223A

  • Circulating fluidized bed slag resource utilization method

    CN114716173A

  • Green cement-based material used in sulfate corrosion environment

    CN116239357A

  • High-performance green cement-based grouting material for leaking stoppage of foundation pit

    CN116332609A

Cited By

  • ECC ratio optimization method and system based on continuous conditional generative adversarial network, and terminal

    CN121328346A